Kinetic beauty the philosophical aesthetics of sport - Holt, Jason (Ethics and sport, 2021)
Sport aesthetics is an important but often marginalized field in the philosophy of sport. Kinetic Beauty offers a comprehensive, principled, pluralist introduction to the philosophical aesthetics of sport. The book tackles a wide variety of issues in the philosophical aesthetics of sport, proposing a five-level analysis that coordinates extant scholarship on the same conceptual map, reveals gaps in the literature, and motivates a fresh perspective on stubborn debates and novel topics in the field (for example, the aesthetic experience of athletes, aesthetic biases in sport, the paradox of sport fiction, and whether dance can be sport). This is an excellent resource for professors and students in the philosophy of sport, sport aesthetics, general aesthetics, and the philosophy of art. It is also a fascinating read for those working in kinesiology, sport studies, philosophy, art, and aesthetics